Feasibility of Using Crystal Geometry for a DOI Scintillation Detector - Valenciaga, Y. (IEEE Trans Radiat Plasma Med Sci, 2017)
We have used simulations and measurements to investigate the feasibility of using slanted scintillator crystal geometries as means to provide depth-of-interaction (DOI) information for a pixelated gamma ray imaging detector. The simulations were performed to estimate the fraction of scintillation light detected by the photodetector as a function of interaction location along the height of crystals with different geometries. In addition, physical measurements of the light output for these crystal geometries were obtained from individual crystals coupled to a solid state photodetector (Philips digital-SiPM DPC-3200). In agreement with previous work, we found a change in light output in the slanted region of the crystals compared to the rectangular region. The results from this study indicate the potential of using slanted crystals to gather DOI information based on light output changes as a function of the location of interaction. An examination of the measured energy spectra for the geometries evaluated here, suggests that for BGO crystals somewhere between 2 or 3 DOI bins could be implemented. Based on these results, we conceived a design for a DOI detector module that consists of two slanted crystals, each read-out by separate SiPM pixels.